AN ANALYSIS OF PRESUPPOSITION IN “OUIJA : ORIGIN OF EVIL MOVIE” : PRAGMATICS APPROACH - nur a'la, sillatul dwi; Zakrimal, Zakrimal (LPPM Universitas Putera Batam, 2020)
This research is a case study which will discuss about presupposition in the film